Korteweg-de Vries Equation in Bounded Domains - Nikolai A. Larkin (Boletim da Sociedade Paranaense de Matemática, 2004)
The goal of this paper is to prove the existence, uniqueness and the energy decay of global regular solutions of the KdV equation in a bounded domain approximating it by the Kuramoto-Sivashinsky equations.